THE IMPACT OF THE DIGITAL ECONOMY ON TAX POLICY IN INDONESIA - Andi Andi (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The development of the digital economy has had a significant impact on taxation policy in Indonesia. Changes in business models, especially through e-commerce and digital financial transactions, pose new challenges for traditional taxation systems, which tend to be less relevant. To deal with these changes, the Indonesian government needs to develop effective regulations to accommodate the dynamics of the digital economy and ensure tax compliance from domestic and international businesses. Initiatives such as the imposition of Value Added Tax (VAT) on digital products and services from foreign companies are one of the concrete steps that are expected to increase state revenue and create tax justice. In addition, strengthening information technology infrastructure and a transparent and efficient tax administration system, as well as educating the public about tax compliance, are important factors that support taxation policies in a sustainable digital economy.